Chromium picolinate modulates nitric oxide pathways but enhances myocardial peroxynitrite formation in a rat heart during metabolic syndrome modeling - Akimov, Oleh; Mykytenko, Andrii; Kostenko, Vitalii (European Journal of Clinical and Experimental Medicine, 2026)
Introduction and aim. Metabolic syndrome (MetS) is a global non-communicable health burden. Chromium picolinate (CRPIC) as modulator of p38 MAPK cascade may have a potential therapeutic effect on MetS. The objective of the present study is to evaluate the effects of CRPIC administration on nitric oxide generation and myocardial levels of nitric oxide metabolites in rats under conditions of metabolic syndrome. Material and methods. The experiment was performed on 24 Wistar rats, which were randomly allocated into four groups (n=6 per group): Group I, the control group; Group II, the metabolic syndrome (MetS) group, in which MetS was induced by providing a 20% fructose solution as the sole source of drinking water for 60 days; Group III, the CRPIC-treated group, receiving CRPIC at a dose of 80 µg/kg; and Group IV, the CRPIC+MetS group, in which CRPIC administration was carried out under conditions of experimentally induced metabolic syndrome. The following biochemical parameters were evaluated: total nitric oxide synthase (NOS) activity, inducible NOS (iNOS) and constitutive NOS (cNOS) activities, arginase activity, nitrite reductase and nitrate reductase activities, as well as the concentrations of nitrites, peroxynitrites, nitrosothiols, and hydrogen sulfide. Results. Administration of CRPIC under MetS conditions resulted in a 38.2% reduction in NOS activity and a 40.2% decrease in iNOS activity, accompanied by a 48.9% increase in cNOS activity compared with the MetS group. CRPIC treatment also reduced arginase activity by 13.2%. While the activity of nitrate reductase remained unchanged, nitrite reductase activity decreased by 37.0%. Furthermore, CRPIC increased nitrite levels by 95.2% and peroxynitrite concentrations by 35.2%, while the content of nitrosothiols was reduced by 49.1%. H2S levels also decreased by 16.8%. Conclusion. Administration of CRPIC on the background of metabolic syndrome modeling alleviates enhanced nitric oxide production from the L-arginine-dependent and L-arginine-independent pathways, but increases peroxynitrite compared to the metabolic syndrome group.